Major response of a peritoneal mesothelioma to nivolumab and ipilimumab: a case report, molecular analysis and review of literature - Reveneau, Marie-Florence; Masliah-Planchon, Julien; Fernandez, Manuel; Ouikene, Abdenour; Dron, Bernard; Dadamessi, Innocenti; Dayen, Charles; Golmard, Lisa; Chauffert, Bruno (Frontiers in Oncology, 2024)
Malignant peritoneal mesothelioma (MPM) is a rare tumor associated with a poor prognosis and a lack of consensus regarding treatment strategies. While the Checkmate 743 trial demonstrated the superiority of first-line nivolumab and ipilimumab over chemotherapy in malignant pleural mesothelioma (MPlM), few studies have assessed the effectiveness of immunotherapy against MPM, due to its rarity. Here, we report a major and sustained 12-month response in a 74-year-old female patient who received the anti-PD-1 nivolumab and the anti-CTLA4 ipilimumab as first-line therapy for diffuse MPM. PD-L1 was expressed and BAP1 expression was lost, as shown by immunohistochemistry, however the BAP1 gene was not mutated. Our findings suggest a role for ICI in non-resectable diffuse MPM exhibiting PD-L1 overexpression and loss of BAP1 expression, and instill new hope in their treatment. To our knowledge, this is the second reported case of dual immunotherapy used as first-line in MPM with a major clinical response. To investigate the clinical outcome, we conducted additional molecular analyses of the MPM tumor and we reviewed the literature on immunotherapy in MPM to discuss the role of PD-L1 and BAP1.